JSPS-10 The Effect of Consumption of Raw Chicken Meat on Humoral Immunity against Campylobacter jejuni in veterinarians and workers in a chicken processing plant - Elisabet Tangkonda; Satoshi Sekiguchi; Meiko Kubo; Satomi Sasaki; Takako Taniguchi; Naoaki Misawai (Hemera Zoa, 2018)
Campylobacter jejuni and C. coli are the leading cause of enteric infections in Japan and many other developed countries, and the public health burden of campylobacteriosis is increasing [1]. Although the epidemiological data in Japan is based on passive surveillance, approximately 2,000 to 3,000 cases per each year have been reported as a foodborne infection since 1982. Many risk factors for Campylobacter transmission have been identified. Handling and consumption of poultry meat are often causing of infection [2, 3]. Since Japanese have a food habitant to eat fresh raw